Suspects' consistency in statements concerning two events when different question formats are used. Issue 1 (23rd August 2016) - Deeb, Haneen; Vrij, Aldert; Hope, Lorraine; Mann, Samantha; Granhag, Pär‐Anders; Lancaster, Gary L. J.
Abstract: Lie detection research has typically focused on reports about a single event. However, in many forensic and security contexts, suspects are likely to report on several events, some of them may be untruthful. This presents interviewers with the challenge of detecting which reports are true and which are not. Varying question format in a second interview, we examined differences in liars' and truth‐tellers' statement consistency about two events. One hundred and fifty participants viewed a meeting in which a noncritical and a critical event were discussed. Truth‐tellers were instructed to be honest in their reports about both events, whereas liars had to lie about the critical event. In the first interview, all participants provided a free recall account. In a second interview, participants either gave another free recall account or responded to specific questions presented sequentially (concerning one event at a time) or nonsequentially (concerning both events simultaneously). Liars' accounts featured fewer repetitions than truth‐tellers for both events, particularly in response to questions presented in nonsequential order. The implications for the use of this question format are discussed.